The Eyes of Argus. The Point of View and Points of View with Respect to Kierkegaard's "Activity as an Author" - Garff, Joakim (KIERKEGAARDIANA, 1991)
The Eyes of Argus. The Point of View and Points of View with Respect to Kierkegaard’s "Activity as an Author"